Mental toughness: The mindset behind sporting Achievement - Sheard, M. (Routledge, 2013)
Mental toughness is one of the most common terms used in sport - by athletes, coaches, spectators and the media. However, it is also one of the least understood terms. This book examines the characteristics and development of mentally tough sport performers, and presents the cutting-edge research in this area. Within these chapters, the author proposes that mental toughness is a personality style and mindset, and presents a compelling case for its inclusion within the positive psychological paradigm. This second edition has been updated to include new material on the characterisation, conceptualisation, measurement, and development of mental toughness. As in the first edition the book includes a historical overview of empirical research, and also describes the conceptual arguments behind this research. Now packed with even more rigorous scientific evidence and bang up-to-date anecdotes from the world of sport, the book presents a fascinating explanation of why some athletes are successful, and how and why they stay on top. Mental Toughness: The Mindset Behind Sporting Achievement will be essential reading for all sport psychology, sport science, sport studies, and coaching students.